Implementation of the strategy of health promoting schools (Ágora de Heterodoxias, 2018)
The present work was aimed to implement the program of Health Promoting Schools in the Fiscal School of the Republic of Cuba, in the Payanchi neighbourhood of the city of Loja, in order to promote individual and collective initiatives and actions to achieve wellness and suitable conditions for a healthy life in the educational community. We worked with the methodology of logical framework, which initially allowed us to identify the main causes for which this school did not work as a health promoter;  from which the actions to be developed throughout the investigation were established to fulfill the objectives. The results obtained were aimed to strengthening four basic areas associated to the proper functioning of the school: public management and participation, development of healthy environments and environmental conditions, health training and provision of health services. Taking into consideration that the school is the ideal place to create a health culture involving personal and social responsibility, highlighting the integrality of the person and the need to provide it with knowledge and tools to reach their possibilities of realization.
Keywords: community participation; health; quality of life; wellness; social organization